Antioxidant Potential of Vitex Doniana Ethanol Leaf Extract In Triton X-100induced Hyperlipidemic Wistar Albino Rats - C. O. Okpala; I. O. Igwilo; F. Eze (The Bioscientist, 2021)
This study was undertaken to investigate the antioxidant potential of ethanol leaf extract of Vitex doniana against Triton X-100 induced hyperlipidaemia in rats. The percentage yield of the leaf was 9.21% w/w. The phytochemical constituents of the extract were identified using the standard method of AOAC. In vitro antioxidant activity of the extract (0.1–0.5 mg/mL) was investigated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, and nitric oxide radical. In vivo antioxidant potential of the extract was evaluated in triton X-100 induced hyperlipidemic and normal rats. The LD50 of the leaves extract was greater than 5000mg/kg body weight. Quantitative analysis of the plant secondary metabolites showed the presence of tannin (32.40±0.02 mg/g), flavonoid (16.87±0.27 mg/g), alkaloid (0.50±0.07 mg/g), cyanogenic glycosides (0.06±0.00 µg/g) and saponin (0.83±0.10mg/g). The result of proximate composition showed the presence of carbohydrate (41.85±0.73 %), protein (19.26±0.12%), fats (12.75±0.41%), moisture (12.04±0.17 %), crude fibre (11.82±0.19 %) and ash (11.90±1.00 %). The extract scavenged DPPH and nitric oxide radical concentration dependently. A total of thirty (30) adult male albino rats were divided into six (6) groups (A, B, C, D, E, and F), with five (5) animals in each group. Group A and B received distilled water only; Group C received 10 mg/kg b. w of atorvastatin while groups D, E, and F received an oral administration of 200, 400 and 600 mg/kg b.w. of Vitex doniana leaf extract, respectively. After 21 days, their blood serums were analysed. A significant (p<0.05) decrease in the concentration of malondialdehyde (MDA) was observed in groups that received atorvastatin and extract when compared to the hyperlipidemic untreated group. The activities of superoxide dismutase (SOD), and catalase (CAT) showed a dose dependent significant (p<0.05) increase when the groups that received extract and atorvastatin were compared to the hyperlipidemic untreated group.